Pasta enriched with de-oiled sesame and yellow pepper flours: Evaluation of physicochemical properties, protein quality, and antioxidant potential - Eman M. Abdo; Amira M.G. Darwish; Marwa M.E. Hussein; Hanem M.M. Mansour (Applied Food Research)
Valorization of waste as a sustainable food additive to produce value-added products is a recent interest. De-oiled sesame flour (DSF) is underutilized despite its rich protein, fiber, and phenols content. Pasta has a poor nutritional value but is a good vehicle for fortification. Therefore, pasta was enriched with DSF at 10 %, 20 %, and 30 %, in addition to 5 % yellow pepper flour (YPF) to improve the taste (S10, S20, and S30, respectively). The enriched pasta was compared to control pasta (S0) made from 100 % durum wheat semolina concerning the sensory attributes, cooking quality, physicochemical properties, and microstructure. S20 pasta demonstrated good cooking properties and a texture profile similar to the control, with high sensory appeal. It had the lowest cooking loss (7.60±0.10), gumminess (39.50±5.12 g), and chewiness (0.62±0.09 mJ), the highest water absorption and volume expansion (101.30±1.27 % and 295.00±7.07 %), a shorter cooking time (10.05±0.71 min) and hardness (73.00±5.66 g), with a moderate cohesiveness (0.54±0.03) (p < 0.05). DSF increased the protein content of the enriched pasta significantly compared to the control (14.40±0.57 g to 16.90±0.57 g versus 13.20±0.28 g/100 g). Besides, the protein quality was improved by adding 20 % DSF: The essential amino acid index increased from 62.76±0.05 % to 73.11±0.95 % in S20 (p < 0.05). Furthermore, the antioxidant activity was increased from 1.67±2.12 % (control) to 28.75±1.53 % (S20) (p < 0.05). Besides, iron, calcium, and zinc were increased considerably (p < 0.05). De-oiled sesame flour at 20 % (S20) is a promising additive for pasta producers that offers acceptable physical changes, high nutritional value, and enhanced protein quality compared to control.